SANG SURYA DI WILAYAH MINORITAS MUSLIM - indria nur; Rusdi Rusdi; Sudirman Sudirman (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
Abstract, Muhammadiyah as a religious organization, is very concerned with the world of education. The presence of Muhammadiyah education in educating the nation's life has been going on for more than a century, since its establishment in 1912. Its educational characteristics, which symbolize the personality of Muhammadiyah, have brought progress in education throughout Indonesia, from Sabang to Merauke. Data were collected through interviews, observation and documentation. From the research results, it is illustrated that the Muhammadiyah education movement advances education in Muslim minority areas, with its educational identity Al Islam and Muhammadiyah, collegiate management patterns and community cooperation. Muhammadiyah with its solar light brings enlightenment to the progress of education in West Papua, not only for the Muslim community but also for non-Muslims. In accordance with Muhammadiyah's khittah as a reformer, the Muhammadiyah Education movement in West Papua is synonymous with inclusive, pluralist, and moderate concepts. This proves that Muhammadiyah has long been enlightening its rays by carrying out tajdid propagation of its culture in the Muslim minority areas of the Earth of Paradise.